Accuracy and repeatability of quantitative fluoroscopy for the measurement of sagittal plane translation and finite centre of rotation in the lumbar spine. Issue 7 (July 2016) - Breen, Alexander; Breen, Alan
Highlights: Quantitative fluoroscopy was validated for measurement of Intervertebral FCR and translation. Accuracy compared with instrumented vertebral models was 2.2 mm or less. Within observer ICCs were moderate to high for translation in human subjects. Within observer SEMs were 1.8 mm or less for FCR and 1.1 mm or less for translation. Within observer ICCs were fair to substantial for translations in human subjects. Abstract: Quantitative fluoroscopy (QF) was developed to measure intervertebral mechanics in vivo and has been found to have high repeatability and accuracy for the measurement of intervertebral rotations. However, sagittal plane translation and finite centre of rotation (FCR) are potential measures of stability but have not yet been fully validated for current QF. This study investigated the repeatability and accuracy of QF for measuring these variables. Repeatability was assessed from L2-S1 in 20 human volunteers. Accuracy was investigated using 10 consecutive measurements from each of two pairs of linked and instrumented dry human vertebrae as reference; one which tilted without translation and one which translated without tilt. The results found intra- and inter-observer repeatability for translation to be 1.1 mm or less (SEM) with fair to substantial reliability (ICC 0.533–0.998). Intra-observer repeatability of FCR location for inter-vertebral rotations of 5° and above ranged from 1.5 mm to 1.8 mm (SEM) with moderate to substantial reliability (ICC 0.626–0.988). Inter-observer repeatability for FCR ranged from 1.2 mm to 5.7 mm, also with moderate to substantial reliability (ICC 0.621–0.878). Reliability was substantial (ICC > 0.81) for 10/16 measures for translation and 5/8 for FCR location. Accuracy for translation was 0.1 mm (fixed centre) and 2.2 mm (moveable centre), with an FCR error of 0.3 mm( x ) and 0.4 mm( y ) (fixed centre). This technology was found to have a high level of accuracy and with a few exceptions, moderate to substantial repeatability for the measurement of translation and FCR from fluoroscopic motion sequences.